Contrasting life history strategies in a phylogenetically diverse community of freshwater amphipods (Crustacea: Malacostraca) - Copilaş-Ciocianu, Denis; Boroş, Bianca V (Zoology., 2016)
Differences in life histories are commonly exhibited within ecological communities, especially among species that display increased variations in body size and morphology and are phylogenetically distant. To examine the relationship between morphological dissimilarity and life history divergence, we investigated three morphologically distinct and distantly related species of freshwater amphipods that co-occur throughout the Danube lowlands - Gammarus balcanicus dacicus, Niphargus valachicus and Synurella ambulans - by collecting monthly samples during a one-year period. Results revealed that the studied species differ significantly with respect to fecundity, size at maturity, number of generations per year, duration and timing of the reproductive period and egg volume. Despite some overlap, each species possesses a unique combination of traits, supporting the hypothesis that life history variation within freshwater amphipod communities can reflect dissimilarities regarding body size, morphology and evolutionary relationships. However, it is not yet clear which of these factors has the most significant contribution to life history divergence.
Keywords: Male; fylogeneze; Reproduction; Phylogeny; Pregnancy; Amphipoda; těhotenství; mužské pohlaví; sladká voda; Rumunsko; Fresh Water; rozmnožování; Animals; ženské pohlaví; Body Size; zvířata; velikost těla; Female; Romania